IFNL3/4 polymorphisms as a two‐edged sword: An association with COVID‐19 outcome. Issue 2 (11th February 2023) - Matic, Sanja; Milovanovic, Dragan; Mijailovic, Zeljko; Djurdjevic, Predrag; Sazdanovic, Predrag; Stefanovic, Srdjan; Todorovic, Danijela; Popovic, Suzana; Vitosevic, Katarina; Vukicevic, Vladimir; Vukic, Milena; Vukovic, Nenad; et al.
Abstract: Coronavirus Disease 2019 (COVID‐19) has been ranked among the most fatal infectious diseases worldwide, with host's immune response significantly affecting the prognosis. With an aim to timely predict the most likely outcome of SARS‐CoV‐2 infection, we investigated the association of IFNL3 and IFNL4 polymorphisms, as well as other potentially relevant factors, with the COVID‐19 mortality. This prospective observational case‐control study involved 178 COVID‐19 patients, hospitalized at Corona Center or Clinic for Infectious Diseases of University Clinical Centre Kragujevac, Serbia, followed up until hospital discharge or in‐hospital death. Demographic and clinical data on all participants were retrieved from the electronic medical records, and TaqMan assays were employed in genotyping for IFNL3 and IFNL4 single nucleotide polymorphisms (SNPs), namely rs12980275, rs8099917, rs12979860, and rs368234815. 21.9% and 65.0% of hospitalized and critically ill COVID‐19 patients, respectively, died in‐hospital. Multivariable logistic regression analysis revealed increased Charlson Comorbidity Index (CCI), N/L, and lactate dehydrogenase (LDH) level to be associated with an increased likelihood of a lethal outcome. Similarly, females and the carriers of at least one variant allele of IFNL 3 rs8099917 were almost 36‐fold more likely not to survive SARS‐CoV‐2 infection. On the other hand, the presence of at least one ancestral allele of IFNL4 rs368234815 decreased more than 15‐fold the likelihood of mortality from COVID‐19. Our results suggest that, in addition to LDH level, N/L ratio, and CCI, IFNL4 rs368234815 and IFNL3 rs8099917 polymorphisms, but also patients' gender, significantly affect the outcome of COVID‐19.